PENGARUH SOAL HIGHER ORDER THINKING SKILL (HOTS) TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA TEMA 8 SUB TEMA 3 DI KELAS IV SEKOLAH DASAR - Agustin Mutia; Agustin Mutia Miftakhul Hasanah; Satrio Wibowo; Budhi Rahayu Sri Wulan (LPPM STKIP PGRI Sidoarjo, 2021)
ABSTRACT The aims of this study are 1. To determine the effect of HOTS questions on students' critical thinking skills on theme 8, sub-theme 3, learning 1 and learning 2 in fourth grade elementary school. 2. To find out the effect of HOTS questions on student learning outcomes in theme 8, sub-theme 3, learning 1 and learning 2 in grade IV SD. 3. To find out student responses to the HOTS questions on theme 8, sub-theme 3, learning 1 and learning 2 in grade IV SD. This type of research is quantitative research with experimental methods. The sample of this study were 11 students of SDN Mojorangagung and 11 students of SDN Kebaron. This study used a written test method to determine the level of critical thinking skills and learning outcomes and a questionnaire to determine student responses. The results of this study prove that there is an effect of HOTS questions on critical thinking skills of 55.7% and obtaining a correlation value of 0.746 indicates a strong relationship level. The results of this study also prove that there is an effect of HOTS questions on student learning outcomes by 49.0% and obtaining a correlation value of 0.700 indicates a strong relationship level. The results of this study also prove that there is a very good response from students, this can be seen through the percentage obtained, namely 89.09%. Keywords: HOTS questions, critical thinking skills, learning outcomes